The expertise reversal effect concerning instructional explanations - Rey, Günter Daniel; Fischer, Andreas (Instructional science, 2013)
The expertise reversal effect occurs when learner’s expertise moderates design principles derived from cognitive load theory. Although this effect is supported by numerous empirical studies, indicating an overall large effect size, the effect was never tested by inducing expertise experimentally and using instructional explanations in a computer-based environment. The present experiment used an illustrated introductory text and a computer program about statistical data analyses with 93 students. Retention and transfer tests were employed as dependent measures. Each learner was randomly assigned to one condition of a 2 × 2 between subjects factorial design with the two factors expertise (novices vs. ‘experts’) and explanations (with vs. without). Expertise was induced by adding expository examples and illustrations to the introductory text to enhance text coherence and facilitate text comprehension. The expertise reversal effect was replicated for the dependent measure transfer, but not for retention. Results and implications for adaptive learning environments are discussed.